2016
DOI: 10.1038/srep33002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing of 248 Chinese aortopathy patients using a panel assay

Abstract: Inherited aortopathy, which is characterized by a high risk of fatal aortic aneurysms/dissections, can occur secondarily to several syndromes. To identify genetic mutations and help make a precise diagnosis, we designed a gene panel containing 15 genes responsible for inherited aortopathy and tested 248 probands with aortic disease or Marfan syndrome. The results showed that 92 individuals (37.1%) tested positive for a (likely) pathogenic mutation, most of which were FBN1 mutations. We found that patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Cysteine substitutions in the calcium-binding EGF-like domains represent the majority of pathogenic missense changes associated with FBN1-related disorders [ 2 ]. Furthermore, other missense variants at the same residue (C1958Y, C1958R) have also been reported in published literature in association with FBN1-related disorders, including assumed de novo occurrences for both variants, supporting the functional significance of this residue [ 15 17 ]. Finally, this variant has not been observed in large population cohorts such as the ExAC (Exome Aggregation Consortium) database [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 77%
“…Cysteine substitutions in the calcium-binding EGF-like domains represent the majority of pathogenic missense changes associated with FBN1-related disorders [ 2 ]. Furthermore, other missense variants at the same residue (C1958Y, C1958R) have also been reported in published literature in association with FBN1-related disorders, including assumed de novo occurrences for both variants, supporting the functional significance of this residue [ 15 17 ]. Finally, this variant has not been observed in large population cohorts such as the ExAC (Exome Aggregation Consortium) database [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 77%
“…More than 900 patients with aortic disease and/or diagnosed or suspected MFS had been referred from the Aortic Surgery Department to the Center for Molecular Diagnosis at Fuwai Hospital and had undergone panel testing involving 15 genes (ACTA2, COL3A1, FBN1, FBN2, MYH11, MYLK, NOTCH1, PRKG1, SKI, SLC2A10, SMAD3, SMAD4, TGFB2, TGFBR1, TGFBR2) since Feb 2014 [9]. Furthermore, more than 200 aortopathy patients were performed whole exome sequencing.…”
Section: Patientsmentioning
confidence: 99%
“…Except that her youngest brother had pectus carinatum and scoliosis, other family members had no obvious skeletal deformities. A 15-gene panel [9] testing revealed that she Note: NA not available; MAF in ExAC was the maximal allele frequency from the public version (20160423), and MAF in gnomAD was the maximal allele frequency from gnomAD v2.1.1; P, pathogenic; LP, likely pathogenic; VUS, variant of uncertain significance; a , reported in our previous article [11]; b This variant was previously misclassified as likely pathogenic [11], and now corrected into VUS carried a TGFBR2 mutation (c.1254G > T, p.Gln418His), which was inherited from her mother, who suffered an aortic dissection at age 42. Therefore, she was highly suspected to be LDS.…”
Section: Paternal Lp Pvs1 Pm2mentioning
confidence: 99%
“…Several studies in which gene panels have been used for clinical diagnosis have reported varying rates of diagnosis. Just some of the diseases studied to date are epilepsy [ 134 , 135 ], metabolic disorders [ 31 , 45 , 136 , 137 ], orodental diseases [ 138 ], neuromuscular disorders [ 139 - 142 ], hereditary immunodeficiencies [ 143 - 144 ], hereditary motor neuropathies [ 145 - 147 ], amyotrophic lateral sclerosis [ 148 ], intellectual disability [ 149 ], hematologic diseases [ 150 , 151 ], skeletal dysplasias [ 152 ], cardiovascular disorders [ 153 - 155 ], hearing loss [ 156 - 157 ], retinal disorders [ 158 - 163 ], sex development [ 164 - 165 ], maturity onset diabetes of the young [ 166 ], ichthyosis [ 167 ], cystic kidney diseases [ 168 ], and aortopathies [ 169 ].…”
Section: Introduction: Advances In the Field Of Rare Diseases Reachedmentioning
confidence: 99%